Paradigma keilmuan Islam di perguruan tinggi - Ummah, Sun Choirol (Universitas Negeri Yogyakarta, 2019)
Science and religion should be able to be completed even if they should be able to work together and complement each other. On the other hand, there is unease among scientists who consider that methodological tools in science cannot be applied in religious studies, or assume that religious values cannot help scientists find the truth. In this case, there are those who still view that both (science and religion) are single entities or positioned as isolated entities. The antithesis of both is seen in the interconnected entities model as a more advanced perspective that touches on the problem of approaches and methods and procedures. There are four typologies of the relationship between science and religion that often arise including; conflict, independence, dialogue and integration. The most recent typology that is widely used is the integration combined with interconnection. It is appropriate for universities in Indonesia to strive to get closer, integrate and connect between science and religion so that the values of life that are in the area of meaning (religion) and want to be achieved can be achieved. Sains dan agama selayaknya dapat dipersandingkan bahkan keduanya seyogyanya mampu bersinergi dan saling mengisi. Di sisi lain, ada kegamangan di antara para ilmuwan yang menganggap bahwa perangkat metodologis dalam ilmu pengetahuan tidak bisa diterapkan dalam kajian keagamaan, atau menganggap bahwa nilai-nilai agama tidak bisa membantu para saintis untuk menemukan kebenarannya. Dalam hal ini ada yang masih memandang bahwa keduanya (ilmu dan agama) merupakan single entity atau diposisikan sebagai isolated entities. Antitesis keduanya terlihat pada model interconnected entities sebagai cara pandang yang lebih maju yang menyentuh persoalan pendekatan (approach) dan metode berfikir serta penelitian (process and procedure). Ada empat tipologi hubungan sains dan agama yang sering muncul diantaranya; konflik, independen, dialog, dan integrasi. Tipologi terkini yang banyak digunakan yakni integrasi yang dikombinasikan dengan interkoneksi. Selayaknya perguruan tinggi yang ada di Indonesia berupaya keras untuk mendekatkan, mengintegrasikan dan mengoneksikan antara sains dan agama sehingga nilai-nilai kehidupan yang berada pada wilayah makna (agama) dan ingin dituju bisa tercapai.